The Opportunities and Threats Resulting from Robotic Process Automation in Public Service Development - Baran, Grzegorz; Berkowicz, Aleksandra; Marzec, Małgorzata; Sasak, Janusz; Szczudlińska-Kanoś, Agnieszka (Journal of Public Governance, 2021)
Objectives: This study aims to identify the opportunities and threats of automation and robotisation process automation in the development of public services.Research Design & Methods: In this study, the method of deduction was used as well as auxiliary methods and techniques such as logical analysis, analysis and study of literature, and classification and scientific description. The reasoning process was based on knowledge of management sciences and the existing findings with regard to digital transformation, in particular the robotic process automation of the public sector and services.Findings: The study revealed opportunities and threats related to the automation and robotisation of public services concerning three entities/groups: citizens, administration employees, and public organisations.Implications: The issues presented in the article might constitute the basis for practitioners, mainly public authorities and all other persons responsible for creating and implementing automated and robotic public services. Applications can be of particular interest to local government officials and management staff of various public institutions. Therefore, the robotisation and automation of services will gain in importance in the coming years, and many entities will be involved in their introduction and operation. This paper can also be useful for the economic and non-governmental sectors, whose recipients will be more aware of the opportunities and threats of service automation and robotisation.Contribution / Value Added: As a result of the analysis, the synthesis of the theoretical findings on the processes of automation and the robotisation of public services as well as certain consequences of these processes for further development of these public services were identified. They were then classified as opportunities or threats to the further automation and robotisation of public services, which may serve as a basis for the establishment of subsequent empirical studies.Article classification: theoretical/conceptual paperJEL classification: M0, O3, H4